2020
DOI: 10.1155/2020/9247451
|View full text |Cite
|
Sign up to set email alerts
|

Viral Suppression and Its Associated Factors in HIV Patients on Highly Active Antiretroviral Therapy (HAART): A Retrospective Study in the Ho Municipality, Ghana

Abstract: Background. The WHO targets to end HIV/AIDS as a public health problem by 2030. The introduction of the ambitious “90-90-90” strategy to attain this target is expected to be achieved by the year 2020. However, there is lack of regional data, especially on the third “90.” This study sought to assess the rate and associated factors of viral suppression among people living with HIV (PLWH) on highly active antiretroviral therapy (HAART) at the Antiretroviral Therapy (ART) Clinic in a Ghanaian health facility. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
3
21
3
Order By: Relevance
“…The small sample size might have affected this finding. This also contrasts with the findings of Lokpo et al (2020) where regular clinic attendance was significantly associated with viral suppression (p=0.0001). This could be due to the practice of giving a week's medication in excess of appointment which makes clients miss appointment dates when they have medications at home.…”
Section: Discussioncontrasting
confidence: 94%
“…The small sample size might have affected this finding. This also contrasts with the findings of Lokpo et al (2020) where regular clinic attendance was significantly associated with viral suppression (p=0.0001). This could be due to the practice of giving a week's medication in excess of appointment which makes clients miss appointment dates when they have medications at home.…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, adherence to clinic visits is closely linked to good adherence to medications [31] . A recent study reports a high proportion of unsuppressed viral load among participants non-adherent to HIV clinic visits and a high proportion of suppressed viral load among those adherent to the visits [25] . Missed clinic appointments have been linked to unsuppressed viral load and delayed immune recovery [32] , [33] .…”
Section: Discussionmentioning
confidence: 98%
“…Our data show that non-adherence to ART clinic visits on one hand, and patient representation, on the other hand, are associated with an increased likelihood of TPT incompletion. Adherence to clinic visits is an important proxy measure for adherence to ART [25] , [26] . ART clinic attendance is an important component of comprehensive HIV care as it enables service providers to track patient clinical progress and offers a valuable opportunity to receive health information.…”
Section: Discussionmentioning
confidence: 99%
“…89 non-suppression out of 284 HIV-positive patients). 11 What this implies is that there might be variations in the proportion of HIV-infected people achieving viral load suppression in different parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found regular ART clinic attendance and treatment >3 years as factors associated with viral suppression. 11 The present study builds on the above studies by determining the rate and factors associated with viral load non-suppression among adults living with HIV/AIDS on active ART at Kumasi in the Ashanti Region of Ghana. Findings could inform policy decisions and strategies in improving care and attaining the 90-90-90 and the 95-95-95 targets.…”
Section: Introductionmentioning
confidence: 99%